2013
DOI: 10.1016/j.bbamcr.2012.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Neil3, the major DNA glycosylase activity for removal of hydantoins in single stranded DNA, reduces cellular proliferation and sensitizes cells to genotoxic stress

Abstract: 7,8-Dihydro-8-oxoguanine (8-oxoG) is one of the most common oxidative base lesions in normal tissues induced by a variety of endogenous and exogenous agents. Hydantoins are products of 8-oxoG oxidation and as 8-oxoG, they have been shown to be mutagenic lesions. Oxidative DNA damage has been implicated in the etiology of various age-associated pathologies, such as cancer, cardiovascular diseases, arthritis, and several neurodegenerative diseases. The mammalian endonuclease VIII-like 3 (Neil3) is one of the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 72 publications
2
31
0
Order By: Relevance
“…This feature of cisplatin-ICLs might result from the massive distortion of the DNA induced by the lesion. It should be noted that Neil3 -nullizygous MEFs exhibit modest sensitivity to cisplatin (Rolseth et al, 2013), suggesting that a portion of cisplatin-ICLs may be processed by NEIL3 in cells. More ICLs will have to be examined to determine whether the degree of distortion is a primary factor in determining pathway choice.…”
Section: Discussionmentioning
confidence: 99%
“…This feature of cisplatin-ICLs might result from the massive distortion of the DNA induced by the lesion. It should be noted that Neil3 -nullizygous MEFs exhibit modest sensitivity to cisplatin (Rolseth et al, 2013), suggesting that a portion of cisplatin-ICLs may be processed by NEIL3 in cells. More ICLs will have to be examined to determine whether the degree of distortion is a primary factor in determining pathway choice.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Accordingly, Takao et al 38 demonstrated that an Escherichia coli strain double mutated for Nth and Nei presents higher sensibility to ROS, and when Neil3 is overexpressed, the resistance was partially recovered. Similarly, Rolseth et al 41 demonstrated that the primary mouse embryonic fibroblast (MEFs), obtained from Neil3 knockout mouse, presented higher sensibility to the genotoxic agents cisplatin and paraquat, when compared to MEFs with normal expression of Neil3. Once secondary DNA damage inflicted from IR is promoted by ROS, our data suggest that similar to Takao et al 38 and Rolseth et al, 41 NEIL3 could play an important role in the resistance of GBM cells to this type of genotoxic stress.…”
Section: Discussionmentioning
confidence: 99%
“…The Sp and Gh lesions in double-stranded DNA are good substrates of BER enzymes in vitro that include the bifunctional DNA glycosylases E. coli Fpg [102], Nei [103], mammalian NEIL1 and NEIL2 [78], NEIL3 [79, 104106], human NEIL1 [71, 72], and human NEIL3 [80]. These hydantoins, are also repaired by the prokaryotic NER pathways initiated by UvrABC proteins in vitro [107].…”
Section: Interplay Between Ber and Ner Pathways In The Repair Of Omentioning
confidence: 99%